(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
The transactional, transformational, and formal legal leadership models of school principals for educators and education staff play an important role in determining the progress of the institution they lead. The purpose of this study is to describe that the leadership style of the principal of SD Muhammadiyah Jogokariyan influences the progress of SD Muhammadiyah Jogokariyan. This study uses descriptive qualitative methods, data collection techniques through observation, interviews, and documentation. The results showed that (1) the Principal of SD Muhammadiyah Jogokariyan applied a transactional leadership style, namely the principal focused on the role of coordinator, supervisor, and team performance appraisal. The principal is responsible for individual performance to achieve the best final result. Principals give awards to teachers who excel as motivation for other teachers. The Principal of SD Muhammadiyah Jogokariyan also applies transformational leadership, which is enthusiastic about helping teachers who have difficulties in classroom administration or other matters related to education in schools so that teachers continue to be enthusiastic in serving in the world of education. (2) a positive leadership style is the right alternative for school progress, namely building a positive school climate, establishing positive relationships between school members and local residents, and positive communication between school residents. (3) The Principal of SD Muhammadiyah Jogokariyan uses a humanist approach by holding regular weekly meetings with school residents or visiting the homes of community leaders to invite together to promote SD Muhammadiyah Jogokariyan